2017
DOI: 10.1073/pnas.1619034114
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between d -3-phosphoglycerate dehydrogenase and d -2-hydroxyglutarate dehydrogenase drives bacterial l -serine synthesis

Abstract: l-Serine biosynthesis, a crucial metabolic process in most domains of life, is initiated by d-3-phosphoglycerate (d-3-PG) dehydrogenation, a thermodynamically unfavorable reaction catalyzed by d-3-PG dehydrogenase (SerA). d-2-Hydroxyglutarate (d-2-HG) is traditionally viewed as an abnormal metabolite associated with cancer and neurometabolic disorders. Here, we reveal that bacterial anabolism and catabolism of d-2-HG are involved in l-serine biosynthesis in A1501 and PAO1. SerA catalyzes the stereospecific red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 54 publications
4
68
0
Order By: Relevance
“…However, given our previous observation that Ser3 and Ser33 reduce αKG to the D enantiomer of this dicarboxylic acid [38], this is most likely also the product of the 3PGA-αKG transhydrogenase activity. While this work was ongoing, other investigators independently showed that the Pseudomonas and E. coli phosphoglycerate dehydrogenases (SerA) also actually act as 3PGA-αKG transhydrogenases that produce D-2HG [52,53], perfectly corroborating our results with the yeast enzymes. Only relatively few examples of transhydrogenases are known so far.…”
Section: Nad(p)hx Repair Deficiency Leads To Discrete Changes In Genesupporting
confidence: 84%
“…However, given our previous observation that Ser3 and Ser33 reduce αKG to the D enantiomer of this dicarboxylic acid [38], this is most likely also the product of the 3PGA-αKG transhydrogenase activity. While this work was ongoing, other investigators independently showed that the Pseudomonas and E. coli phosphoglycerate dehydrogenases (SerA) also actually act as 3PGA-αKG transhydrogenases that produce D-2HG [52,53], perfectly corroborating our results with the yeast enzymes. Only relatively few examples of transhydrogenases are known so far.…”
Section: Nad(p)hx Repair Deficiency Leads To Discrete Changes In Genesupporting
confidence: 84%
“…However, given our previous observation that Ser3 and Ser33 reduce αKG to the D enantiomer of this dicarboxylic acid , this is most likely also the product of the 3PGA‐αKG transhydrogenase activity. While this work was ongoing, other investigators independently showed that the Pseudomonas and E. coli phosphoglycerate dehydrogenases (SerA) also actually act as 3PGA‐αKG transhydrogenases that produce D‐2HG , perfectly corroborating our results with the yeast enzymes. Only relatively few examples of transhydrogenases are known so far.…”
Section: Discussionsupporting
confidence: 85%
“…This indicated that EtfAB-I was first reduced to form the red anionic semiquinone with pseudooxynicotine by Pno, and the subsequent decrease of absorption at 370 nm was caused by the formation of fully reduced hydroquinone (33). In order to quantify the activity of EtfAB-I, we added DCPIP to investigate the effects of EtfAB-I on the reduction of DCPIP with pseudooxynicotine by Pno (where PMS was omitted), as described previously (34). Increased DCPIP-reducing activity was observed when purified EtfAB-I was added (Fig.…”
Section: Resultsmentioning
confidence: 99%